DEFECTIVE CALCIUM PUMPS IN NEURONS IN THE AGING BRAIN AND IN PARKINSON’S DISEASE - Asma Zaidi; Sidrah Sheikh; Shaneisha Williams; Paul Ramlow (European Scientific Journal, ESJ, 2015)
The plasma membrane Ca2+-ATPase (PMCA) pumps play an important role in the maintenance of precise levels of intracellular Ca2+, quintessential for the optimal functioning and long term survival of neurons. In this paper, we review evidence showing alterations in the PMCAs in aging brain. Additionally, we provide evidence showing defects in these transporters in Parkinson’s disease (PD). PMCA activity and protein levels in brain synaptic plasma membranes (SPMs) decline progressively with increasing age. The PMCAs undergo functional and structural changes when exposed to reactive oxygen species known to be generated in the aging brain and in neurodegenerative disorders such as PD. The major changes in the PMCAs include rapid inactivation, formation of aggregates, internalization from the plasma membrane and fragmentation by proteases. Reduction of PMCA levels as occurs in aging and under conditions of oxidative stress may play an important role in compromised neuronal function in the aging brain and in PD. Therapeutic strategies that protect the PMCAs and stabilize [Ca2+]i homeostasis have the potential of serving as novel interventions in preventing and/or slowing down the degeneration of neurons in various chronic neurodegenerative disorders.